Respuesta :

4(2² + 2(-2)) - 2(-2) = 4(4-4) + 4 = 4*0 + 4 = 4

The given expression is [tex]4(a^2 + 2b) - 2b[/tex]. when a = 2 and b = –2 then the answer would be 4.

What is a simplification of an expression?

Usually, simplification involves proceeding with the pending operations in the expression.

Like, 5 + 2 is an expression whose simplified form can be obtained by doing the pending addition, which results in 7 as its simplified form.

Simplification usually involves making the expression simple and easy to use later.

The given expression is

[tex]4(a^2 + 2b) - 2b[/tex]

when a = 2 and b = –2.

[tex]4(2^2 + 2(-2)) - 2(-2) \\\\ =4(4-4) + 4 \\\\= 4\times 0 + 4 = 4[/tex]

Learn more about the factored form of an expression here:

https://brainly.com/question/1249625

#SPJ2

ACCESS MORE